From Malakah To Deep Learning: Contextualizing Ibn Khaldun For Modern Educational Practice - Amaliyah, Intan Nur Fauziyah; Fahmi, Muhammad; Munawwaroh, Siti Nafilatul (Universitas Islam Indonesia, 2025)
This study aims to examine Ibn Khaldun's concept of malakah in relation to the philosophy of deep learning based on the principles of mindful, meaningful, and joyful learning. The study is motivated by the need for an educational approach that emphasizes depth of understanding, critical reflection, and character building. Using comparative literature review method, this study draws primarily on the Muqaddimah as it main source and analyze it through systematic comparison with contemporary deep learning framework. Data were analyzed using content analysis techniques involving stages of data reduction, theme categorization, and comparative interpretation. The results of the study indicate a strong conceptual convergence between malakah and deep learning, especially in the process of internalizing knowledge through sustained practice, guided repetition, and reflective dialogue. This study contributes by proposing malakah-Deep Learning Integration, a synthetic framework that maps the integration of cognitive, affective, and psychomotor, and connects the spiritual-moral dimensions of malakah with the development of 21st-century competencies associated with deep learning. This framework provides a philosophical-pedagogical foundation of more holistic and contextually grounded model of Islamic education. This study recommends further empirical studies to examine the practical effectiveness of this conceptual framework in educational settings.